MODEL PENINGKATAN KAPASITAS PENYULUH DALAM PEMANFAATAN INFORMASI IKLIM DI KABUPATEN INDRAMAYU DENGAN PENDEKATAN ANALISIS KEBERLANJUTAN - Humaedah, Ume; Yulianti, Astrina; Sirnawati, Enti; Efendi, Lukman (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Capacity of extension agents in understanding climate forecasting and climate change is allegedly limited. Therefore, it is necessary to improve their capacity on this issue. Research was conducted between May to December 2014. Indramayu in West Java was choosen purposively, representing irrigated-land agroecosystem. Respondents were extension agents selected from Agricultural Extension of Fisheries and Forestry Services (BP3K) or Agricultural Extension Services (BPP)with their working area being considered high vulnerability to climate change. Total respondents were 59 extension agents randomly selected. There were three phases of dynamic hypothesis resulting in : 1) problem identification, 2) ideal capacity determination; and 3) model design. Methods of data collection were survey, interview, and focus group discussion (FGD). A RAP-FISH ordination technique through Multi Dimensional Scaling (MDS) was used to assess the existing extension capacity and identify sensitive attributes influencing the ability of the extension agents in the use of climate information through analysis of leverage in each variable. Results showed that accessibility to resources, information management and election of extension dimension methods were the dimensions to be considered for improving the extension agents capacity building in climate utilization. Therefore, a structural approach should be done through increased synergy between institutions involved in capacity building of extension agents and its resources. Moreover, synergy amongst sources of information should be conducted to encourage the roles of BP4K and BP3K in managing climate information. While the functional approach is done through re-designing capacity development activities on utilizing climate information, with the focus on improving the accessibility, information management, and selection of extension methods.